Magyar magánjogászok tudományos írásai Németországban (1920–1944) - Herger, Csabáné (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2022)
The study of the scientific relations between Hungarian and German private law jurists between 1920 and 1944 is still a current research issue, the comprehensive presentation of which has not been undertaken by either the German or the Hungarian legal historians. This research task cannot be completely performed by the author of this study either. The research question is that among the Hungarian private jurists, who published his scientific results in German journals, in the columns of the Zeitschrift der Akademie für Deutsches Recht and in the Zeitschrift für osteuropäisches Recht, and on what topics and in what way was it approached. The study covers private law in the broad sense, so in addition to general private law, it also covers writings on family law, commercial law and civil procedure law. When evaluating these questions, the role of the given author in Hungarian scientific public life is also a research aspect.